1994
DOI: 10.5951/at.41.6.0318
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Classroom Portfolio Assessment

Abstract: Three years ago, the mathematics teachers from grades 4-12 in our school met for two weeks during the summer for an in-service program related to assessment and decided to begin using portfolios with our students in the fall. I was enthusiastic, although I had no idea at that time how drastically my approach to assessment—and to teaching in general—would change a a result of the portfolio decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Likewise, Tasdemir et al [ 4 ] showed that the group for which portfolio evaluation along with cooperative learning was applied became more successful in passing the course than the other groups. Lambdin and Walker [ 17 ] concluded that the portfolio evaluation method increases self-assessment ability in students and makes them more independent in comparison to their classmates. In this research, scores on higher cognitive level question (analysis and judgment) were significantly greater for the portfolio group than the routine evaluation group.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Tasdemir et al [ 4 ] showed that the group for which portfolio evaluation along with cooperative learning was applied became more successful in passing the course than the other groups. Lambdin and Walker [ 17 ] concluded that the portfolio evaluation method increases self-assessment ability in students and makes them more independent in comparison to their classmates. In this research, scores on higher cognitive level question (analysis and judgment) were significantly greater for the portfolio group than the routine evaluation group.…”
Section: Discussionmentioning
confidence: 99%
“…ainda o uso da Metacognição, pode-se propor a utilização de Mapas Conceituais (RODRÍGUEZ, 1997; SANTOS, 1997; NOVAK; CAÑAS, 2010), ou a elaboração de Diários (DARSIE, 1996; RODRÍGUEZ, 1997; SANTOS, 1997), ou Portfolios (LAMBDIN;53WALKER, 1994;PONTE, 1997;SANTOS, 1997). Desta forma, caminha-se verdadeiramente em busca da compreensão dos conceitos matemáticos.A proposição da diversificação das Tarefas de Avaliação não é para aumentar o trabalho do Docente, e sim para diversificar a forma de observar o aluno, recolher evidências do seu desenvolvimento educativo matemático.…”
unclassified
“…: Gibson & Barrett, 2003 ;Abrami, Barrett, 2005;Smith, Tillema, 2003 ;Wade , Abrami, Sclater, 2005;Zeichner, Wray, 2001;Teitel, Ricci and Coogan, 1998 ;Wolf & Dietz , 1998 Asturias, 1994 ;Crowley, 1993 ;Lambdin & Walker, 1994 ;Stenmark, 1991 . ) - Leal, 1997, 11;Stenmark,1999 (Riedinger ,2006,97;Klenowski,Askew Carnell, 2006 ;Boud's , 2000,151 ;Moseley and Ramsay ,2005;Hilliard ,1991, (Davis & Honan, 1998 ;Freidus, 1998 ;Zeichner & Wray, 2001;Young, J. R.,2002,380;Helen.…”
mentioning
confidence: 99%